Financial amplification of foreign exchange risk premia - Tobias Adrian; Erkko Etula; Jan J. J. Groen (Federal Reserve Bank of New York, 2010)
Theories of systemic risk suggest that financial intermediaries' balance-sheet constraints amplify fundamental shocks. We provide supportive evidence for such theories by decomposing the U.S. dollar risk premium into components associated with macroeconomic fundamentals and a component associated with financial intermediary balance sheets. Relative to the benchmark model with only macroeconomic state variables, balance sheets amplify the U.S. dollar risk premium. We discuss applications to systemic risk monitoring.
Keywords: G15; G01; G17; F31; 330; Foreign exchange risk premium; systemic risk monitoring; financial intermediation; asset pricing; Wechselkursrisiko; Risikoprämie; US-Dollar; Finanzintermediär; Capital Asset Pricing Model; USA; Welt